Immunohormonal interactions in patients with vulvar cancer - G. A. Nerodo; T. V. Mironenko; A. M. Tyutyunova (ABV-press, 2014)
A parallel study of some parameters of the endocrine and immune systems was conducted in 120 patients with vulvar cancer prior to treatment.Most patients were found to have impaired immunogenesis: the reduced count and function of T and B lymphocytes, decreased natu- ral killer cells, suppressed macrophageal transformation of monocytes, higher percentage of immunocomplexes, insufficient production of immunoglobulins (IgA, IgM, IgG), which was induced by the elevated level of cortisol in its slower metabolism at the periphery, reduced function of the pituitary-thyroid system, the balance of sex steroids shifted towards testosterone, a predominance of luteiniz- ing hormone over follicle-stimulating hormone, and inhibited growth hormone production.